Structure-property relationships in Bi2O3-TiO2-B2O3glasses modified with BaO: toward lead-free radiation shielding materials - Deng, Hongyi; Gan, Rongguang; Miyazaki, Hidetoshi; Bergler, Michael; Oka, Ryohei; de Ligny, Dominique; Hayakawa, Tomokatsu; Cicconi, Maria Rita (Ceramics International, 2025)
In this study, a series of lead-free, Bi-based glasses were designed and investigated for potential applications in radiation shielding. The glasses, based on the system xBaO-(90-x)(40Bi2O3-25TiO2-35B2O3)-10Al2O3(x = 0-30 mol%), were synthesized via a melt-quenching process at 1000 °C. The physical and optical properties of the glasses, as well as the valence states of Bi and the local oxygen environments, were systematically explored. The non-linear variation in physical and optical properties with composition is explained by the structural changes related to Bi, Ti, and B, as revealed by Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and solid-state nuclear magnetic resonance (NMR) spectra. Simulations of radiation shielding ability were performed using the XCOM tool. The simulation results show that the glasses exhibit high mass attenuation coefficients (MAC), reaching up to 4 cm2/g, and low half layer value (HLV), reaching 0.031 cm at 100 keV photon energy, which are better than many previously reported Bi-containing glass systems. As photon energy increases, MAC values decrease and HLV increases, as expected. The addition of BaO slightly reduces the MAC and increases the HLV, while it can modify physical and optical properties, including density, glass stability, refractive index, optical band gap, ultraviolet-visible (UV-vis) absorption, and luminescence behavior, thereby offering flexibility for different applications in medical field and nuclear industry. Moreover, when the BaO content reaches 30 mol%, the glass exhibits optimal transparency and is almost colorless. These results suggest that the studied glass system is a promising candidate for lead-free radiation shielding applications, combining high MAC, low HLV with tunable physical and optical characteristics.
CRIS-Team Scopus Importer:2025-12-26
Keywords: Bismuth-boron glass; Lead free; Optical properties; Radiation shielding